Intimate Partner Violence Perpetration, Victimization, and Overlap Among Serious Juvenile Offenders: Trajectories of Emerging Adulthood - Richards, Tara N. (Journal of interpersonal violence, 2021)
This study uses group-based trajectory analysis and data from the Pathways to Desistance Study to examine the prevalence and patterns of intimate partner victimization, offending, and overlap among justice-involved adolescents (i.e., general offenders) who reported dating (n = 909); regression analysis was further utilized to assess predictors of intimate partner violence (IPV) group membership. Findings revealed that 40% of adjudicated youth reported IPV as a victim, an offender, or as both a victim and an offender during emerging adulthood. Findings also indicated that there was significant overlap between victimization and offending, and 5% of the sample was assigned to both the high-rate perpetration and victimization trajectory groups. Maternal hostility, alcohol use, and witnessing violence predicted higher rate perpetration and victimization overlap group membership compared with very-low-rate perpetration/victimization group membership. Implications for informing policy and future research are discussed.